Basic & clinical immunology - Hugh, Fudenberg, H.;Stites, Daniel P.;Caldwell, Joseph L.;Wells, J. Vivian (Los Altos, California : Lange Medical Publications, 1978)
The clinical chapters focus on primary immunologic diseases or on disorders with important immunopathologic characteristics.
Section I. Basic immunology -- Section II. Immunobiology -- Section III. Immunologic laboratory tests -- Section IV. Clinical immunology.
Includes index.
Keywords: IMMUNOLOGIC DISEASES